2018
DOI: 10.3748/wjg.v24.i17.1888
|View full text |Cite
|
Sign up to set email alerts
|

Oral treatment with plecanatide or dolcanatide attenuates visceral hypersensitivity via activation of guanylate cyclase-C in rat models

Abstract: AIMTo investigate the effects of plecanatide and dolcanatide on maintenance of paracellular permeability, integrity of tight junctions and on suppression of visceral hypersensitivity.METHODSTransport of fluorescein isothiocyanate (FITC)-dextran was measured to assess permeability across cell monolayers and rat colon tissues. Effects of plecanatide and dolcanatide on the integrity of tight junctions in Caco-2 and T84 monolayers and on the expression and localization of occludin and zonula occludens-1 (ZO-1) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 42 publications
0
21
0
1
Order By: Relevance
“…These patients reported a median satisfaction score for treatment of 4.0 (quite satisfied) and were “quite likely” to continue the medication. Animal models suggest that plecanatide, similar to linaclotide, also reduces visceral sensitivity 101 , and phase 3 trials in patients with IBS-C have demonstrated a significant improvement in bowel motion frequency, stool consistency, and abdominal pain above that seen with placebo 102 . Sustained response with the 6 mg dose of plecanatide was seen in 30% of patients in the first study (placebo response 18%, p <0.001) and 24% in the second trial (14% placebo response, p <0.001) 102 .…”
Section: Development Of Novel Therapeutic Agents For the Treatment Ofmentioning
confidence: 99%
“…These patients reported a median satisfaction score for treatment of 4.0 (quite satisfied) and were “quite likely” to continue the medication. Animal models suggest that plecanatide, similar to linaclotide, also reduces visceral sensitivity 101 , and phase 3 trials in patients with IBS-C have demonstrated a significant improvement in bowel motion frequency, stool consistency, and abdominal pain above that seen with placebo 102 . Sustained response with the 6 mg dose of plecanatide was seen in 30% of patients in the first study (placebo response 18%, p <0.001) and 24% in the second trial (14% placebo response, p <0.001) 102 .…”
Section: Development Of Novel Therapeutic Agents For the Treatment Ofmentioning
confidence: 99%
“…Chang and others (Chang et al, 2017) showed that orally administered plecanatide reduced the degree of inflammation-driven colonic dysplasia in mice (Chang et al, 2017). In accordance with these findings, Boulete and others (Boulete et al, 2018) indicated that activation of GC-C signaling may be an attractive therapeutic approach to treat functional constipation disorders and inflammatory gastrointestinal conditions (Boulete et al, 2018). Recent studies reported that GC-C agonists plecanatide and linaclotide can be used in the treatment of chronic idiopathic constipation (Lembo et al, 2011;Islam et al, 2018).…”
Section: Introductionmentioning
confidence: 87%
“…Delayed gastric emptying through sympathetic activation (36,137) Increased active ghrelin concentration (137,139,140) Hypersensitivity (134)(135)(136) Hyperpermeability through re-organization of the cytoskeleton (134) Changes in mucosal morphology and decrease of glial cells in the submucosa plexus Increased immune cells infiltration (MC Eo)…”
Section: Stress-related Models Of Fgidmentioning
confidence: 99%
“…This protocol is mostly used as an acute stressor with a 1 to 2 h period of restraint. However, this short exposure already promoted (1) colonic hypersensitivity ( 134 136 ), (2) an increased influx of immune cells in the mucosa, mostly consisting of mast cells and eosinophils ( 135 ), (3) an intestinal hyperpermeability through the reorganization of the cytoskeleton in epithelial cells ( 134 ), (4) a delayed gastric emptying associated with the stress-induced sympathetic activation, increased CRF ( 36 , 137 ) and associated peptides ( 138 ) as well as active ghrelin concentration ( 137 , 139 , 140 ), and (5) changes in colonic morphology and a decrease of enteric glial cells especially in the submucosa plexus ( 135 ). By using this model for 14 days, Yi et al could demonstrate the implication of the insular cortex in stress-induced visceral hypersensitivity, a region found to be abnormally activated in FGID patients ( 19 ) and more in general in patients with chronic pain ( 141 ).…”
Section: Stress-related Models Of Fgidmentioning
confidence: 99%